The man who smiled - Mankell, Henning, 1948-2015 (Mankell, Henning, 1948-2015. Kurt Wallander mystery, 2006)
"The Man Who Smiled begins with Wallander deep in a personal and professional crisis after killing a man in the line of duty; eventually, he vows to quit the Ystad police force for good. Just then, however, a friend who had asked Wallander to look into the death of his father winds up dead himself, shot three times. Ann-Britt H?glund, the department?s first female detective, proves to be his best ally as he tries to pierce the smiling fa?ade of his prime suspect, a powerful multinational business tycoon. But just as he comes close to uncovering the truth, the same shadowy threats responsible for the murders close in on Wallander himself"--Publisher website (December 2006).